The Effects of Innovation on Employment in Developing Countries Evidence from Enterprise Surveys - Cirera, Xavier (World Bank E-Library Archive, 2016)
While existing evidence in advanced economies suggests a possible role for technological innovation in job creation, its role in developing countries remains largely undocumented. This paper sheds light on the direct impact of technological as well as organizational innovation on firm level employment growth based on the theoretical model of Harrison, Jaumandreu, Mairesse, and Peters (2014) using a sample of over 15,000 firms in Africa, South Asia, Middle East and North-Africa and Eastern Europe and Central Asia. The results suggest that new sales associated with product innovations tend to be produced with just as much or higher levels of labor intensity. The effect is largest in lower income countries and the African region, where firms are further away from the technological frontier. More importantly, process innovations that involve automation of production do not have a short-term negative impact on firm employment. However, there is some evidence of a negative effect of automation on employment that manifests in increases in efficiency that reduce the elasticity of new sales to employment. Overall, these results are qualitatively similar to previous findings in advanced economies and highlight a positive direct role of innovation on the quantity of employment but at a decreasing rate as firms' transition to the technological frontier